1972
DOI: 10.1017/s0003356100011247
|View full text |Cite
|
Sign up to set email alerts
|

Fleece characteristics and postnatal fleece development in Finnish Landrace × Merino sheep

Abstract: SUMMARY1. Fleece characteristics in Finnish Landrace × Merino and Merino × Finnish Landrace sheep were compared with those of the parental breeds, and although most characters in the crossbreds showed no significant departure from the parental mean, they had similarities to the Merino which imparted commercial value.2. The wool was mostly of 60s quality compared with 58s in the Finnish Landrace, and 64s and over in the Merino parents. Crimp number showed heterosis, being 5 to 6 per cm in the crossbreds compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Gjedrem (1969) found the male lambs to have finer wool but in adult sheep the difference between sexes was reversed. Ryder and Wilson (1972) found also coarser fibres in the females in Finnsheep x Merino crosses. Sumner and Bigham (1993) reported slightly greater FD in rams with the difference between the sexes increasing with age.…”
Section: Fixed Effectsmentioning
confidence: 73%
“…Gjedrem (1969) found the male lambs to have finer wool but in adult sheep the difference between sexes was reversed. Ryder and Wilson (1972) found also coarser fibres in the females in Finnsheep x Merino crosses. Sumner and Bigham (1993) reported slightly greater FD in rams with the difference between the sexes increasing with age.…”
Section: Fixed Effectsmentioning
confidence: 73%
“…Genetic correlations quoted by Brown and Turner (1968) for Merino sheep show a high negative correlation between density and diameter. Ryder and Wilson (1972) who reported on crosses of the Finnish Landrace with the Tasmanian Merino, and McGuirk et al (1978) who studied crosses of Border Leicester and Australian Merino, found little evidence of heterosis in the corresponding components of fleece and skin. Rae (1958), however, reports what may amount to a stronger correlation of fleece weight with diameter than with staple length, the diameter-related measure in this case being quality number (a visual assessment of fineness).…”
Section: Discussionmentioning
confidence: 99%
“…Among the wool-producing breeds a major difference occurs between the Merino types and the rest (see, for example, Carter and Clarke, 1957a and b), but even within each of these types there is great variability in fineness of wool, length of staple, and fleece weight (Ryder and Stephenson, 1968). There is little published information on the subject of ieterosis but some studies have reported this (see Ryder and Wilson, 1972;McGuirk, Bourke and Manwaring, 1978). There is little published information on the subject of ieterosis but some studies have reported this (see Ryder and Wilson, 1972;McGuirk, Bourke and Manwaring, 1978).…”
mentioning
confidence: 99%
“…Adalsteinsson's hypothesis is, however, likely to apply to all Scandinavian sheep, and so the appearance of black lambs in pure Finnish Landrace and Finnish Landrace h Merino sheep (Ryder & Wilson, 1972) is of interest because no black animals have been observed in the ABRO Merino flock. Assuming that the Finnish Landrace has the B, gene this implies that the (almost invariably white) Merino also carries the B, or B, gene, which is normally suppressed.…”
Section: Discussionmentioning
confidence: 99%